Respuesta :
Answer:
a=[tex]\frac{2}{3}[/tex],b=[tex]-\frac{2}{3}[/tex]
Step-by-step explanation:
Original=[tex]\frac{(\sqrt{7} -1)^{2} }{7-1} -\frac{(\sqrt{7} +1)^{2} }{7-1}[/tex]
=[tex]\frac{(\sqrt{7} -1)-(\sqrt{7} +1)^{2} }{6}[/tex]
=[tex]\frac{(\sqrt{7}-1+\sqrt{7} -1)(\sqrt{7} -1 -\sqrt{7} -1)}{6}[/tex]
=[tex]\frac{-4\sqrt{7} +4}{6}[/tex]
=[tex]\frac{2}{3} -\frac{2}{3} \sqrt{7}[/tex]
Contrast factor
a+b√ 7=[tex]\frac{2}{3} -\frac{2}{3} \sqrt{7}[/tex]
and so a=[tex]\frac{2}{3}[/tex],b=[tex]-\frac{2}{3}[/tex]
Step-by-step explanation:
Hi friend!!
√7-1/√7+1 – √7+1/√7-1
→ (√7-1)/(√7+1) × (√7-1)/(√7-1) – (√7+1)/(√7-1) × (√7+1)/(√7+1)
→ (√7-1)²/(√7+1)(√7-1) – (√7+1)²/(√7-1)(√7+1)
→ {√7²+1²-2(√7)(1)}/(√7²-1²) – {√7²+1²+2(√7)(1)}/(√7²-1²)
→ (7+1-2√7)/6 – (7+1+2√7)/6
→ (8-2√7)/6 – (8+2√7)/6
→ {8-2√7-8-2√7}/6
→ -4√7/6
→ 0+(-2/3)√7 = a+√7b
Therefore, a = 0 and b = -⅔
Hope it helps.